"Deep questions for a Saturday morning": An investigation of the Australian and Canadian general public's definitions of gender. (10th August 2021) - Hall, Jennifer; Jao, Limin; Di Placido, Cinzia; Manikis, Rebecca
Abstract: Objective: Many studies exist about people's views of gender in a wide variety of fields. However, participants are not typically asked what they think gender means; rather, gender is presumed to have a taken‐as‐shared meaning. Methods: As part of a larger study conducted in Australia and Canada about the general public's views of gender and mathematics, we investigated participants' definitions of the term gender . We considered overall trends and trends by demographic group (country, gender, age, and education level). Results: Most commonly, gender was defined as a person's feelings or self‐identification. Participants also frequently solely used the terms male and female or discussed biological features. However, response patterns varied widely by demographic group. Conclusion: Due to these diverse and sometimes contradictory definitions, we argue that researchers cannot assume that participants have common understanding of the term gender . We conclude by providing suggestions for how gender‐focused research can be done in more transparent ways.